Dinâmica social, econômica e territorial na distribuiç\~ao modal de viagens urbanas: Evidências do município de S\~ao Paulo - Carlos Henrique Ribeiro de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This work sought to identify the socioeconomic, urbanistic and mobility variables that explain the higher relative occurrence of trips by public transport (TPU - transporte público coletivo urbano), individual motorized transport (TI - transporte individual motorizado) and non-motorized transport (TNM - transporte n\~ao motorizado) in S\~ao Paulo. The evidence was worked from data from the S\~ao Paulo origin and destination survey. It was observed that denser neighborhoods with a greater diversity of jobs and enrollment favor the use of TPU and TNM. Places with a higher proportion of formal jobs also show a higher use of TPU. On the other hand, income is an important factor for defining the modal matrix, favoring TI in the richest regions. In dormitory regions, predominantly residential, TPU still prevails, but with the increase in the rate of motorization and the process of gentrification of neighborhoods, there is a strong impact in favor of TI. There are some indications of public policies in the urban and economic scope in the sense of prioritizing TPU and TNM in order to arrive at sustainable mobility policies.
Keywords: R42; 330; urban transport planning; modal distribution; land and use; urban densification; public transportation; urban development; non-motorized transport; urban trips